Age and Rate of Accumulation of Metal‐Rich Hydrothermal Deposits on the Seafloor: The Lucky Strike Vent Field, Mid‐Atlantic Ridge. Issue 6 (31st May 2022) - Sánchez‐Mora, Dennis; Jamieson, John; Cannat, Mathilde; Escartín, Javier; Barreyre, Thibaut
Abstract: Hydrothermal venting at the Lucky Strike hydrothermal field, located on the Mid‐Atlantic Ridge, is associated with faulting linked to the tectonic dismemberment of a central axial volcano. Radium‐226/Ba dating of hydrothermal barite indicates that hydrothermal venting is at least 6, 600 years old, and that Lucky Strike is one of the youngest known vent fields on the Mid‐Atlantic Ridge, which typically have ages exceeding 20 ka. Deposit volume calculations indicate that the total accumulated mass of the hydrothermal deposits on the seafloor at Lucky Strike is ∼1.3 ± 0.2 Mt, and that this mass accumulated at a maximum average rate of 194 ± 28 t/yr. This accumulation rate is comparable to other well characterized mid‐ocean ridge hydrothermal sites, such as TAG and Endeavor, but at Lucky Strike is concentrated within a relatively small area of <2.5 km 2 . Plain Language Summary: In this contribution we determine the age (>6, 600 years) and mass (∼1.3 Mt) of metal‐rich deposits that formed at a cluster of high‐temperature seafloor hot springs called Lucky Strike, which is situated on the Mid‐Atlantic Ridge. With this information we calculate the average rate of formation (194 t/yr) of these deposits. Our results indicate that the Lucky Strike vent field is much younger than other vent fields that also occur along the Mid‐Atlantic Ridge, but the deposits form at similar rates, which are high when compared to other types of geological processes that produce metal‐rich deposits. Key Points: Hydrothermal activity at the Lucky Strike vent field has been ongoing for at least 6, 600 years An estimated ∼1.3 Mt of hydrothermal material has accumulated on the seafloor over an area of <2.5 km 2 of seafloor, at a rate of ∼194 t/yr Accumulation rates from Lucky Strike are comparable to other seafloor sites and to analogous on‐land volcanogenic massive sulfide deposits